ANALISIS SISTEMPERAWATAN UNIT MULTIFLO MF420EX MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI PT KLM - Adam Alfath; Ainur Komariah, Suprapto (PROSIDING, 2022)
PT KLM is a coal mining company. The obstacle experienced by PT KLM in the period January 2018 to July 2019 in the Dewatering section was the high frequency of unscheduled breakdowns in the Multiflo MF420EX unit. This breakdown resulted in the low performance of the pump engine. As a result, the sump water level rises and closes the coal loading area. This research uses the Reliability Centered Maintenance method. This study aims to detect failure modes, MTBF and maintenance actions on 3 critical components. From this study, data were obtained for 7 components that experienced failure mode, data for 3 components that had the highest RPN value, and MTBF data. The three components are fuel filter 350, gland packing 80, and rubber mounting panel 72. The results of the MTBF calculation show that the MTBF value for the fuel filter component is 216.76 hours, gland packing 471.69 hours, and rubber mounting panel 886.67 hours. . The recommended action for maintaining the fuel filter is to modify the fuel tank by giving a hole in the tank bulkhead for easy cleaning and adding tank cleaning in the maintenance sheet item every 250 hours. The recommendation for gland packing care is to add it to the periodic inspection sheet every 3 days and replace it in the maintenance sheet every 500 hours. The recommendation for maintenance of rubber mounting panels is to add it to the periodic inspection sheet every 3 days and replace it in the maintenance sheet every 750 hours. Keywords: Maintenance, MF420EX unit, reliability centered maintenance.